Analysis of the Level of Consumer Satisfaction with the JR Connexion Bus Transportation Service on the Cibubur - Blok m route - Muhammad Sylmi Taufanudin; Muhammad Isradi; Andri Irfan Rifai (NAROTAMA UNIVERSITY, Indonesia, 2021)
This study aims to determine the level of performance, the level of consumer satisfaction with the services provided by the JR Connexion Bus route Kota Wisata Cibubur - Blok M and to determine the physical condition of the JR Connexion Bus. The research method was carried out by collecting primary data and secondary data by conducting on-bus surveys which included load factor, headway, frequency, travel speed, travel time, service time, passenger waiting time and number of vehicles operating. For service performance and satisfaction, it is analyzed based on the Standards of the Directorate General of Transportation, as well as service data which is then analyzed using qualitative and quantitative analysis methods. Regarding the extent to which the quality of performance and service level of passenger satisfaction with the JR Connexion Bus route Cibubur - Blok M is used Importance Performance Analysis (IPA). Then tested the effect of service performance with the level of customer satisfaction using the Chi-Square (X²) formula. Based on the results of the analysis, it was concluded that the operational performance of the JR Connexion Bus for the Cibubur - Blok M tourist city route according to the Directorate General of Land Transportation was in the